PENGARUH UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP KOEFISIEN RESPON LABA - Efrinal Efrinal; Reni Astuti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study analyzes the Effect of Firm Size and Growth Opportunity on Earning Response Coefficient on the Jakarta Islamic Index Company in 2015-2021. Multiple linear regression analysis in this research is used SPSS 26 of the independent variables, namely the firm size and growth opportunity on the dependent variable, namely the earnings response coefficient. Exchange for the 2015-2021 period, using the purposive sampling method, 12 sample companies were obtained and 84 observers passed the criteria. The data used is the annual report of each sample company published through www.idx.co.id. The results show that Firm Size has a negative effect on the Earnings Response Coefficient and Growth Opportunity has a positive effect on the Earnings Response Coefficient.